Description of the air quality in the Navarro Dumpsite area of influence, in Cali, Colombia. (Colombia Medica, 2008)
Background: This study evaluated emissions from the municipal open dump in Cali, the Navarro dump (ND), and their effects in air quality of an area defined as exposed (< 3 km distance and downwind) as compared with a control zone (>3 km and upwind). Methods: Sample collection was carried out with semiautomatic equipments following approved international procedures accepted by local environmental laws. Sampling was carried out simultaneously in the study zones during three climatologic periods: dry, rainy and inter-season periods. Ten samples were taken during each period, for a total of 30 samples per zone. Particulate matter below 10 micras, SO2, methane and volatile organic compounds: benzene, toluene and xilene were measured in each sample. Results: Results showed sources of methane and benzene are mainly inside the ND and are carried by wind dispersion to the exposed zone of the study. There is evidence of a gradient in benzene concentrations starting in the ND (p< 0.01). Benzene concentrations were high in the exposed zone (median=2.92 µg/m3) and 48% of samples collected there were above the maximum level of air quality norm. These measurements were higher that those made in the control zone (median=1.54 µg/m3) where only 22% of the samples were above the maximum levels. Methane also showed decreasing concentrations from exposed to control zone, and there was also a higher concentration of particle matter < 5 micras in the exposed area. Conclusions: Our study gives evidence of environmental effects in areas < 3 km distant of a dump site. This distance should be considered when defining the perimeter of a non inhabited area around municipal solid waste disposals.